PENGARUH PERBANDINGAN JUMLAH TEPUNG KETAN DAN TERUNG BELANDA TERHADAP KARAKTERISTIK DODOL. - Bangun, Enda Yudhi P; Subardjiati, Imaculata; Ina, Ni Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA)
The aim of this research is to determine the effect of comparison between amount of sticky rice flour and tamarillo on the characteristics of dodol and to know the right comparison between amount of sticky rice flour and tamarillo to produce dodol with the best characteristics. The research design with used is randomized group design with comparisons between the amount of sticky rice flour and tamarillo were: 100%:0%, 85%:15%, 70%:30%, 55%:45%, and 40%:60%. Treatments were repeated three times to obtain 15 units of the experiment and the data were analyzed by variance analysis. If there was any impact on the treatment, analysis was followed by Duncan’s test. The result of the research have shown that comparison between the amount of sticky rice flour and tamarillo had significant affects on water content, total sugar content, acidity (pH), fat content, antocyanin content, color, texture, flavor, taste, and overall acceptance. The best characteristics of dodol tamarillo was found on comparison between 55% sticky rice flour and 45% tamarillo with the following criteria: water content 16,45% wb, total sugar content 45,98% wb, acidity (pH) 4,66, fat content 7,18% wb, antocyanin content 8,05mg/100g, protein content 4,29% wb, texture slightly elastic, and the acceptance of color, aroma, taste, overall acceptance are like
Keywords: sticky rice flour, tamarillo, dodol